ANALISIS KINERJA KEUANGAN PERUSAHAAN PROPERTI YANG TERDAFTAR DI BEI SEBELUM DAN SESUDAH KEBIJAKAN LOAN TO VALUE - Prima, Ghaniy Ridha; Siregar, Hermanto; Syarifuddin, Ferry (Economic Faculty, Attahiriyah Islamic University, 2019)
The purpose of this study is to provide empirical evidence of the effects of the Loan to Value (LTV) policy on the financial performance of property and real estate companies listed on the Indonesia Stock Exchange (IDX). The sample selection uses a purposive sampling method of 42 property and real estate companies that meet the criteria. The research period is divided into 2 namely before the Loan to Value policy (2013-2014) and after the Loan to Value policy (2016-2017) with the Paired Sample t Test analysis technique. The test results show if the current ratio, Return on Asset, Return on Equity and Debt to Asset have significant differences between before and after the LTV policy is applied. While the fast ratio, cash ratio, net profit margin and Debt to Equity did not show a significant difference. Keywords: Financial Performance, Loan to Value, Property and Real Estate, Profitability Ratio, Liquidity Ratio, Solvability Ratio.